Implementasi Literasi Informasi Di Sekolah - Mashuri, Ilham (Pustakaloka, 2011)
Lately the term information literacy is often discussedthis awareness needs to be appreciated. Even in Indonesia it canbe said to be late, but considering the importance of the benefits of information for the development of the awareness that literacy should be developed. Information literacy is defined as oneâs knowledge of the needs information, the ability to identify, seek, evaluate, organize and effectively create, use and communicate information for solving problems. Those Knowledges are a prerequisite to live in an information society and part of oneâs basic right to lifelong learning. In a number of libraries that have implemented information literacy, some progress has been achieved. Indeed it is still limited in higher education, sothat information literacy programs in schools should be encouraged and realized. This literacy can be done through various programs: through user education during new student orientation, incidental activity, or to integrate IL into the school curriculum. To realize this agenda all librarians should continue to learn and develop their competences. Without it, they are impossible to carry out information literacy at the school.